2012
DOI: 10.3389/fpls.2012.00263
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of Slow and Quick Anion Channels (SLACs and QUACs/ALMTs)

Abstract: Electrophysiological analyses conducted about 25 years ago detected two types of anion channels in the plasma membrane of guard cells. One type of channel responds slowly to changes in membrane voltage while the other responds quickly. Consequently, they were named SLAC, for SLow Anion Channel, and QUAC, for QUick Anion Channel. Recently, genes SLAC1 and QUAC1/ALMT12, underlying the two different anion current components, could be identified in the model plant Arabidopsis thaliana. Expression of the gene produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
153
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(162 citation statements)
references
References 59 publications
8
153
1
Order By: Relevance
“…For example, three members in Arabidopsis (AtALMT6, AtALMT9, and AtALMT12) and one in barley (Hordeum vulgare; HvALMT1) contribute to guard cell function by transporting organic and inorganic anions across the plasma membrane or tonoplast. This is consistent with the involvement of anion transport in signal transduction and osmotic adjustment in modulating stomatal aperture (Kovermann et al, 2007;Gruber et al, 2010;Meyer et al, 2010;Sasaki et al, 2010;Dreyer et al, 2012;Xu et al, 2015). Electrophysiological studies in Xenopus laevis oocytes revealed similarities between the currents generated by AtALMT12 and the previously characterized rapid or R-type/QUAC anion currents (Hedrich, 2012).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…For example, three members in Arabidopsis (AtALMT6, AtALMT9, and AtALMT12) and one in barley (Hordeum vulgare; HvALMT1) contribute to guard cell function by transporting organic and inorganic anions across the plasma membrane or tonoplast. This is consistent with the involvement of anion transport in signal transduction and osmotic adjustment in modulating stomatal aperture (Kovermann et al, 2007;Gruber et al, 2010;Meyer et al, 2010;Sasaki et al, 2010;Dreyer et al, 2012;Xu et al, 2015). Electrophysiological studies in Xenopus laevis oocytes revealed similarities between the currents generated by AtALMT12 and the previously characterized rapid or R-type/QUAC anion currents (Hedrich, 2012).…”
supporting
confidence: 64%
“…The aluminum-activated malate transporter (ALMT) family of genes encode anion channels in plants, with 14 members in the Arabidopsis (Arabidopsis thaliana) genome and nine in rice (Oryza sativa; Delhaize et al, 2007b;Barbier-Brygoo et al, 2011;Dreyer et al, 2012;De Angeli et al, 2013). The family is named after the first member to be identified, TaALMT1, which controls the major mechanism for aluminum (Al 3+ ) resistance in wheat (Triticum aestivum; Sasaki et al, 2004).…”
mentioning
confidence: 99%
“…When expressed under the control of the SLAC1 promoter, SLAH1 and SLAH3 are able to rescue the slac1-2 stomatal phenotype (Negi et al, 2008). By contrast, SLAH2, which is the closest homolog of SLAH3 (Dreyer et al, 2012), did not complement the phenotype caused by the loss of the chloride-and nitrate-permeable SLAC1 (Negi et al, 2008). This raises the question of whether SLAH2 exhibits different biophysical properties or interacting regulators than those identified in SLAH3 and SLAC1.…”
Section: Introductionmentioning
confidence: 64%
“…The crystal structure of Hi-TehA, a bacterial homolog of SLAC1, suggests that an inner five-helix transmembrane ring forms the pore with a central phenylalanine residue, which is invariant in this superfamily and seemingly blocks the pore (Chen et al, 2010;Dreyer et al, 2012). Whereas wild-type Hi-TehA showed no ion transport when expressed in oocytes, mutation of the blocking phenylalanine residue (Phe-262) to alanine rendered this channel constitutively active (Chen et al, 2010).…”
Section: Homology Modeling Of Slac1 and Slah2 To Reveal Potential Sitmentioning
confidence: 99%
“…In addition to SLAC1, Arabidopsis guard cells also express SLAH3, a second S-type anion channel 25 , which is especially important for the extrusion of NO 3 À . In contrast to S-type channels, R-/QUAC-type anion channels may be essential for the efflux of organic acids such as malate, which can accumulate during stomatal opening and be released during closure [26][27][28] .…”
mentioning
confidence: 99%